Linking Intra- and Inter-Country Spatial Price Adjustments in Global Poverty Measurement : Urban PPP Bias and Reference Price Mismatch - Nakamura, Shohei; Yoshida, Nobuo (World Bank, Washington, DC, 2021)
Measuring global poverty requires two types of spatial price adjustments: inter-country price adjustment based on the international purchasing power parities (PPPs) and intra-country price adjustment to account for cost-of-living variations in different parts of a country, especially between urban and rural areas. Current global poverty measurement lacks an adjustment mechanism for this within-country price variation for many countries, particularly in Sub-Saharan Africa. This paper highlights the need for matching reference prices with those the International Comparison Program (ICP) uses for PPP calculation to avoid poverty estimation bias, largely because many countries collected 2011 ICP price information only in urban areas. Data from four Sub-Saharan African countries are used to show that potential bias in estimated poverty rates due to such reference price mismatches ranges from 0.3 to 6.2 points in absolute terms. A larger bias is observed in countries where gaps between urban and rural prices are greater. The analysis also shows potentially large bias due to lack of intra-country price adjustments. These potential biases underscore the urgent need for conducting within-country price adjustments and matching purchasing power parity reference prices with country spatial price deflators. An important first step is to identify what reference prices the 2011PPPs used for each country, which currently is not clear. The World Bank, with ongoing relationships with National Statistics Offices, is well positioned to take up this task to improve the accuracy of the methodology for estimating poverty at the global, regional, and national levels.